New Flows in Global TV - Moran, Albert (Intellect Books, 2009)
New Flows in Global TV provides a pioneering investigation into television distribution worldwide and the global trade in television program formats. Topics include explorations of how shows like Who Wants to Be a Millionaire? and Big Brother are reformatted for audiences in diverse markets such as Argentina, South Africa, the Middle East, and China; the international circulation of Dallas in the 1980s; and Australian and United Kingdom programming exports in the last decade. Moran argues that distribution is the crucial link in a chain that dictates the consumption and purchase of television content. Consequently, New Flows in Global TV will be a key text for scholars of global media, providing comprehensive insight into the cultural, social and economic exchanges underlying media programming.
Keywords: 1-TV; 2-Étude des industries culturelles; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); _Nettoyé

Slave Revolt on Screen: the Haitian Revolution in Film and Video Games - Sepinwall, Alyssa Goldstein (Caribbean studies series, 2021)
In Slave Revolt on Screen: The Haitian Revolution in Film and Video Games author Alyssa Goldstein Sepinwall analyzes how films and video games from around the world have depicted slave revolt, focusing on the Haitian Revolution (1791–1804). This event, the first successful revolution by enslaved people in modern history, sent shock waves throughout the Atlantic World. Regardless of its historical significance however, this revolution has become less well-known—and appears less often on screen—than most other revolutions; its story, involving enslaved Africans liberating themselves through violence, does not match the suffering-slaves-waiting-for-a-white-hero genre that pervades Hollywood treatments of Black history. Despite Hollywood’s near-silence on this event, some films on the Revolution do exist—from directors in Haiti, the US, France, and elsewhere. Slave Revolt on Screen offers the first-ever comprehensive analysis of Haitian Revolution cinema, including completed films and planned projects that were never made. In addition to studying cinema, this book also breaks ground in examining video games, a pop-culture form long neglected by historians. Sepinwall scrutinizes video game depictions of Haitian slave revolt that appear in games like the Assassin’s Creed series that have reached millions more players than comparable films. In analyzing films and games on the revolution, Slave Revolt on Screen calls attention to the ways that economic legacies of slavery and colonialism warp pop-culture portrayals of the past and leave audiences with distorted understandings.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé; _À nettoyer; _À vérifier-Cinéma

Sovereign Words: Indigenous Art, Curation and Criticism - García-Antón, Katya (Office for Contemporary Art Norway, 2018)
Artists and cultural practitioners from Indigenous communities around the world are increasingly in the international spotlight. As museums and curators race to consider the planetary reach of their art collections and exhibitions, this publication draws upon the challenges faced today by cultural workers, Indigenous and non-Indigenous, to engage meaningfully and ethically with the histories, presents and futures of Indigenous cultural practices and world-views. Sixteen Indigenous voices convene to consider some of the most burning questions surrounding this field. How will novel methodologies of word/voice-crafting be constituted to empower the Indigenous discourses of the future? Is it sufficient to expand the Modernist art-historical canon through the politics of inclusion? Is this expansion a new form of colonisation, or does it foster the cosmopolitan thought that Indigenous communities have always inhabited? To whom does the much talked-of 'Indigenous Turn' belong? Does it represent a hegemonic project of introspection and revision in the face of today's ecocidal, genocidal and existential crises?"--Page 4 de la couverture. Autres auteurs/titres:edited by Katya García-Antón ; contributors, Daniel Browning, Kabita Chakma, Megan Cope, Santosh Kumar Das, Hannah Donnelly, Léuli Māzyār Luna'i Eshrāghi, David Garneau, Biung Ismahasan, Kimberley Moulton, Máret Ánne Sara, Venkat Raman Singh Shyam, Irene Snarby, Ánde Somby, Megan Tamati-Quennell, Prashanta Tripura, Sontosh Bikash Tripura.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Decolonizing the Spirit in Education and Beyond: Resistance and Solidarity - Wane, Njoki Nathani; Todorova, Miglena S; Todd, Kimberly L (Palgrave Macmillan, 2021)
This multidisciplinary collection probes ways in which emerging and established scholars perceive and theorize decolonization and resistance in their own fields of work, from education to political and social studies, to psychology, medicine, and beyond
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 5-Auteur.rice; 5-Auteur.rice PANDC; 5-Auteur.rice autochtone; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Femmes et violence de masse. - Myre, Nadia; Uzel, Jean-Philippe (Hors-série, 2018)
"Si tous les groupes humains sont touchés par la violence à grande échelle, les femmes la subissent sous des formes spécifiques, comme en témoignent les assassinats systémiques des femmes et des filles autochtones en Amérique du Nord et en Amérique latine, ou encore les nombreux conflits armés (Syrie, Lybie, Birmanie, entre autres) dans lesquels le viol est érigé en arme de guerre. Les deux phénomènes peuvent d'ailleurs se recouper puisque l'un des tout premiers féminicides à avoir été qualifié et documenté comme tel en Amérique est celui ayant été perpétré contre les femmes mayas durant la guerre civile guatémaltèque au début des années 1980. Cependant, les femmes ne sont pas seulement les victimes de la violence de masse, puisqu'elles sont aussi les premières à témoigner et dénoncer pour faire barrage à cette violence. Ce numéro hors-série regroupe des articles et des projets visuels qui décrivent et analysent la violence de masse liée au genre. Il s'agit de réfléchir sur la manière de représenter cette violence et d'en témoigner, d'autant plus qu'elle est bien souvent rendue invisible et inaudible par le patriarcat, le colonialisme, les intérêts politiques en présence ou l'impéritie de l'État."
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Teresa Margolles: mundos - Margolles, Teresa; Uzel, Jean-Philippe; Garcia, Emeren; Zeppetelli, John; St-Gelais, Thérèse; Morales, Lourdes (Musée d'art contemporain de Montréal, 2017)
Violence and the dead are major thematics in the sociopolitical art of Teresa Margolles. Born in Culiacan, Mexico, Margolles unfalteringly exposes the social causes and consequences of the endemic violence that ravages her country: violent deaths from the drug trade, exclusions, feminicides, and social injustice. Many of her works consist of substances or objects that have been in close contact to violent crimes and dead bodies, such as water with which corpses have been cleaned, blood-soaked earth, or fabric drenched in body fluids. This monograph brings together works from the past decade, along with pieces that have never been shown before, including sculptural and photographic installations, performative interventions and videos. Spare, yet powerfully moving, Margolles's work reaches out and brings the viewer into the world of those whose lives have been made invisible.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé

Oubliées ou disparues : Matérialiser absences et mémoires - Graff, Julie (ICOFOM Study Series, 2020)
L’exposition Öndia’tahterendih, oubliées ou disparues : Akonessen, Zitya, Marie et les autres, créée par la Boite Rouge Vif, une OBNL autochtone du Québec, et la commissaire wendate Sylvie Paré, présente 10 artistes rendant hommage aux femmes et aux filles autochtones touchées par le féminicide autochtone, tout en cherchant à mobiliser le public. Je souhaite dans le cadre de cet article explorer les stratégies mises en place au sein de l’exposition, telle qu’elle a été présentée au musée de la Civilisation du Québec en 2018. Je conclurai en explorant l’inscription de l’exposition dans le développement d’un commissariat engagé autochtone au Canada.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Absorbing or Obscuring the Absence of a Critical Space in the Americas for Indigeneity: The Smithsonian's National Museum of the American Indian - Rickard, Jolene (Res: Anthropology and Aesthetics, 2007)
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; _Nettoyé

Décoloniser l’imaginaire esthétique : Vers une écriture de nouveaux paradigmes caribéens - Kirchner-Blanchard, Catherine; Lefrançois, Frédéric (Revue d'Études Décoloniales, 2018)
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 3-Amérique du Sud (corpus analysé); 5-Auteur.rice noir.e; 5-Créateur.rice PANDC; _Nettoyé

Épistémologies du Sud, pensées et féminismes décoloniaux latino-américains - Coenga-Oliveira, Danielle (Revue Possibles, 2019)
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

El color de la razón: racismo epistemológico y razón imperial - Castro-Gómez, Santiago; Eze, Emmanuel Chukwudi; Henry, Paget (Ediciones del Signo, 2014)
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé

Décolonisant l'argent à Porto Rico - Negrón-Muntaner, Frances (revue Periferias, 2019)
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Recherche-création; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice PANDC; 5-Identités diasporiques; _Nettoyé

Introduction de feminismos desde abya yala - Gargallo, Francesca (Revue d'Études Décoloniales, 2020)
Quand les conditions requises pour le dialogue ne sont pas réunies, il est difficile d’expliquer à une femme blanche : " écoute, nous ne voulons pas qu’on nous impose des de critères féministes hégémoniques " . Cela étant, je reconnais et j’apprécie tout ce que j’ai appris sur les différents courants féministes. Car grâce à eux, je me reconnais comme sujette épistémique et je peux me penser à partir du corps et de l’espace où je vis. Ou encore tisser des idées féministes. C’est ainsi que la construction consciente de mon identité féministe communautaire se renforce et en même temps, nous contribuons au mouvement féministe dans le monde. Par exemple, l’une des étapes que nous devons franchir passe par la langue : nommer dans nos propres langues, qui auront été libérées, les catégories et les concepts que nous élaborons pour analyser l’oppression subie par notre peuple dans l’histoire et notre libération en tant que femmes indigènes, autochtones, paysannes, rurales, ou villageoises. Francesca Gargallo est une écrivaine et féministe autonome italo-mexicaine. Licenciée en philosophie de la Sapienza de Rome et docteure en Études Latinoaméricaines de l’UNAM mexicaine, cette spécialiste de l’histoire des idées féministes, prenant acte de l’échec de l’utopie socialiste, propose de chercher des alternatives à partir d’un féminisme clairement antiraciste, qui fasse la critique de l’ eurocentrisme. Elle s’intéresse au concept de colonialisme interne de Pablo González Casanova, ou de Silvia Rivera Cusicanqui. Le livre dont nous traduisons deux extraits, Feminismos desde Abya Yala. Ideas y proposiciones de las mujeres de 607 pueblos en NuestraAmérica, a été publié en 2012 aux éditions Desde abajo.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice; _Nettoyé

Double Desire: Transculturation and Indigenous Contemporary Art - McLean, Ian (Cambridge Scholars Publishing, 2014)
ouble Desire challenges the tendency by critics to perpetuate an aesthetic apartheid between Indigenous and Western art. The double desire explored in this book is that of the divided but also amplified attractions that occur between cultural traditions in places where both indigenous and colonial legacies are strong. The result, it is argued, produces imaginative transcultural practices that resist the assimilation or acculturation of Indigenous perspectives into the dominant Western...
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Océanie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Àbadakone: feu continuel = continuous fire - Dickenson, Rachelle; Hill, Greg A.; Lalonde, Christine (Musée des beaux-arts du Canada, 2020)
Ce survol de l'art contemporain indigène, qui connut un succès retentissant dès son ouverture en novembre 2019, a été prolongé jusqu'au 4 octobre au Musée des beaux-arts du Canada. Àbadakone permet de découvrir des œuvres de plus de 70 artistes qui revendiquent leur appartenance à quelque 40 nations, ethnies et tribus de 16 pays, dont le Canada. Traitant des thèmes de la continuité, de l'activation et de l'interdépendance, Àbadakone explore la créativité, les préoccupations et la vitalité qui marquent l'art indigène de presque tous les continents. L'exposition est organisée par les conservateurs du Musée des beaux-arts du Canada Greg A. Hill, Christine Lalonde et Rachelle Dickenson, conseillés par les commissaires Candice Hopkins, Ariel Smith et Carla Taunton, ainsi que par une équipe d'experts du monde entier. .
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Ensayos de crítica feminista en nuestra América - Mendoza, Breny (Editorial Herder, 2019)
El feminismo hegemónico latinoamericano entró en crisis en los años noventa por su creciente contubernio con el Estado liberal, así como por su práctica política carente de teoría. No supo cómo responder a los desaires de la izquierda masculinista y quedó intacto por los nuevos teóricos de la descolonialidad. Su acción y pensamiento no sólo se manifestaron profundamente colonizados por Occidente, sino que no encontraron una voz clara para entrar en diálogo con ciertas corrientes del feminimo latinoamericano que cuestionaron sus postulados de género, raza y heteronormatividad.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

Le jardin en ville, le cas des Jardins éphémères à Québec. Stratégie marchande et critique postcoloniale - Pageot, Édith-Anne (Globe, 2012)
Cet article se penche sur la portée philosophique du projet intitulé Jardins éphémères, un ensemble de onze jardins temporaires réalisés dans le cadre des activités visant à célébrer le 400ₑ anniversaire de la fondation de la ville de Québec au cours de l’été 2008. L’organisation, les intentions et les principaux thèmes sous-jacents aux différents projets sont présentés dans leur ensemble. Le jardin intitulé « Wampum 400 », créé par deux artistes autochtones, Domingo Cisneros et Sonia Robertson Piekuakamilnu, fait l’objet d’un commentaire plus long. L’analyse montre que le projet Jardins éphémères dans son ensemble incarnait les principaux enjeux actuels du jardin en ville. Certains aspects reconduisaient la vision idéelle du jardin, d’autres satisfaisaient la logique touristique de l’événement et d’autres, enfin, développaient une position critique qui concerne la réappropriation d’un espace à usage collectif et, du coup, interrogeaient les fondements épistémologiques et ontologiques du « jardin ».
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Unsettled Landscapes - Dees, Janet; Hofmann, Irene; Hopkins, Candice; Sanromán, Lucia (SITE Santa Fe, 2014)
Published by SITE Santa Fe on occasion of the inaugural SITElines Biennial, 'Unsettled Landscapes'. Unsettled Landscapes was curated by Janet Dees, Irene Hofmann, Candice Hopkins, and Lucía Sanromán. The exhibition, featuring 47 artists from 14 countries, looks at the urgencies, political conditions and historical narratives that inform the work of contemporary artists across the Americas--from Nunavut to Tierra del Fuego. Through three themes--landscape, territory, and trade--this exhibition expresses the interconnections among representations of the land, movement across the land, and economies and resources derived from the land."--Résumé de l'éditeur
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; 5-Identités diasporiques; _Nettoyé

Feminismos disidentes en América Latina y el Caribe // Féminismes dissidents en Amérique latine et aux Caraïbes - Curiel, Ochy; Falquet, Jules; Masson, Sabine (Editions Antipodes, 2005)
La idea de elaborar un número sobre las luchas de las mujeres y las feministas en América Latina y el Caribe surgió de un encuentro entre Sabine Masson (Suiza), Jules Falquet (Francia) y Ochy Curiel (República Dominicana), cuyos caminos se cruzaron en el continente latinoamericano por razones personales y políticas. Debatimos y reflexionamos juntas sobre la cuestión de las barreras de "raza" y de clase que nos atraviesan a las feministas de diferentes partes del mundo, y que son en particular el reflejo de las relaciones de dominación entre el Sur y el Norte. Precisamente por estas barreras, las experiencias políticas y el trabajo de construcción colectiva de muchas feministas y mujeres, especialmente de América Latina y el Caribe, siguen siendo desconocidas para la mayoría de las feministas de otras latitudes, y de poco interés para las revistas académicas feministas de los países ricos. Oponerse a esta invisibilización y contribuir, aunque sea a nivel experimental y muy modesto, a la deconstrucción de estas barreras, fue nuestra principal motivación para organizar este número en una revista francófona como Nouvelles Questions Féministes. Sin embargo, el trabajo de coordinación presentó importantes contradicciones: primero, entre nosotros mismos. En primer lugar, tuvimos que reconocer e integrar las diferencias y similitudes de nuestras respectivas posiciones, para llegar a un consenso que nos permitiera desarrollar esta cuestión juntos. En segundo lugar, nos enfrentamos al riesgo de reproducir una vez más el saqueo de los conocimientos de las mujeres indias, afrodescendientes y mestizas latinoamericanas y caribeñas por parte de los "expertos del Norte". Los textos se traducirían al francés, lo que significaría que una ínfima minoría de mujeres latinoamericanas y caribeñas tendría acceso a ellos, mientras circulaban por Europa, enriqueciendo una vez más el conocimiento de las mujeres de los países ricos con el trabajo, las luchas, las historias y los escritos de las mujeres de los países pobres. Ante este problema, decidimos que la publicación de este número fuera acompañada de una versión en español, con el objetivo de hacer circular y compartir esta producción intelectual en América Latina y el Caribe L’idée de faire un numéro sur les luttes de femmes et les luttes féministes en Amérique latine et aux Caraïbes a surgi de la rencontre entre Sabine Masson (Suisse), Jules Falquet (France) et Ochy Curiel (République Dominicaine), dont les chemins se sont croisés sur le continent latino-américain pour des raisons personnelles autant que politiques. Nous avons débattu et réfléchi ensemble sur la question des barrières de « race » et de classe qui nous traversent, nous les féministes de différentes parties du monde, et qui sont notamment le reflet des rapports de domination entre le Sud et le Nord. Justement à cause de ces barrières, les expériences politiques et le travail de construction collective de beaucoup de féministes et de femmes, notamment latino-américaines et des Caraïbes, demeurent inconnus de la plupart des féministes d’autres latitudes, et intéressent peu les revues féministes académiques des pays riches. S’opposer à cette invisibilisation et contribuer, même si ce n’est qu’à un niveau expérimental et très modeste, à déconstruire ces barrières, a constitué notre principale motivation pour organiser ce numéro dans une revue francophone comme Nouvelles Questions Féministes . Néanmoins, le travail de coordination présentait d’importantes contradictions : d’abord, entre nous. Pour commencer, nous avons dû reconnaître et intégrer les différences et les similitudes de nos positions respectives, afin de parvenir à un consensus qui nous permette d’élaborer ce numéro ensemble. Ensuite, nous nous confrontions au risque de reproduire encore une fois le pillage des connaissances des femmes indiennes, afro-descendantes et métisses latino-américaines et des Caraïbes par les « expertes du Nord ». Les textes allaient être traduits en français, c’est-à-dire qu’une infime minorité de femmes latino-américaines et des Caraïbes pourrait y avoir accès, pendant qu’ils circuleraient en Europe, enrichissant une fois de plus le savoir des femmes des pays riches à partir du travail, des luttes, des histoires et des écrits des femmes des pays pauvres. Face à ce problème, nous avons décidé que la publication de ce numéro allait s’accompagner d’une version en espagnol, dans le but de faire circuler et de partager cette production intellectuelle en Amérique latine et aux Caraïbes
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Flora and Fauna Otherwise: Black and Brown Aesthetics of Relation in Firelei Báez and Wangechi Mutu - Alvarado, Leticia (Latin American and Latinx Visual Culture, 2019)
Pairing Dominican-born artist Firelei Báez with Kenyan-born artist Wangechi Mutu, this article meditates on relational black and brown aesthetic strategies by reading femme gestures performatively across individual works, as well as the exhibition spaces within which the artists draft practices of informed and resistant engagement. Working with both theories of brownness that emerge from Latinx studies as well as scholarship of the black radical tradition, the author follows a sense of shared aesthetic gestures in Báez and Mutu’s work toward an indictment of pervasive Global North racial epistemologies. Focusing on the performative gesture as the basis for relation, this article ultimately hones in on the chimeric figures—amalgamations of flora and fauna—that both artists deploy, arguing that these present a model for imagining an otherwise arrangement of the social.R Poniendo en diálogo a Firelei Báez, una artista nacida en República Dominicana, con Wangechi Mutu, que nació en Kenia, este artículo invita a una meditación sobre las estrategias estéticas relacionales negras y morenas mediante una lectura en clave performativa de gestos femeninos en obras individuales y en aquellos espacios de exposición en que las artistas elaboran prácticas de participación política informada y de resistencia. Trabajando tanto con las teorías de lo moreno (brownness) que emergen de los estudios Latinx como con el trabajo académico de la tradición radical negra, la autora rastrea gestos estéticos presentes tanto en el trabajo de Báez como en el de Mutu para denunciar las omnipresentes epistemologías raciales del norte global. Centrándose en el gesto performativo como la base de la relación, este artículo se enfoca en última instancia en las figuras quiméricas – amalgamaciones de flora y fauna – que ambas artistas despliegan en su trabajo para sostener que estas presentan un modelo para imaginar otra manera de organizar lo social.
Keywords: 1-Histoire de l'art; 2-Analyses formalistes; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

Sexual Futures, Queer Gestures, and Other Latina Longings - Rodriguez, Juana Maria (New York University Press, 2014)
"Sexual Futures, Queer Gestures and Other Latina Longings proposes a theory of sexual politics that works in the interstices between radical queer desires and the urgency of transforming public policy, between utopian longings and everyday failures. Considering the ways in which bodily movement is assigned cultural meaning, Juana Maria Rodriguez takes the stereotypes of the hyperbolically gestural queer Latina femme body as a starting point from which to discuss how gestures and forms of embodiment inform sexual pleasures and practices in the social realm. Centered on the sexuality of racialized queer female subjects, the book's varied archive--which includes burlesque border crossings, daddy play, pornography, sodomy laws, and sovereignty claims--seeks to bring to the fore alternative sexual practices and machinations that exist outside the sightlines of mainstream cosmopolitan gay male culture. Situating articulations of sexual subjectivity between the interpretive poles of law and performance, Rodriguez argues that forms of agency continually mediate among these various structures of legibility--the rigid confines of the law and the imaginative possibilities of the performative. She reads the strategies of Puerto Rican activists working toward self-determination alongside sexual performances on stage, in commercial pornography, in multi-media installations, on the dance floor, and in the bedroom. Rodriguez examines not only how projections of racialized sex erupt onto various discursive mediums but also how the confluence of racial and gendered anxieties seeps into the gestures and utterances of sexual acts, kinship structures, and activist practices. Ultimately, Sexual Futures, Queer Gestures, and Other Latina Longings reveals--in lyrical style and explicit detail--how sex has been deployed in contemporary queer communities in order to radically reconceptualize sexual politics"--
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Visual Disobedience: The Geopolitics of Experimental Art in Central America, 1990-Present - Cornejo, Kency (N.D., 2014)
This dissertation centers on the relationship between art and politics in postwar Central America as materialized in the specific issues of racial and gendered violence that derive from the region's geopolitical location and history. It argues that the decade of the 1990s marks a moment of change in the region's cultural infrastructure, both institutionally and conceptually, in which artists seek a new visual language of experimental art practices to articulate and conceptualize a critical understanding of place, experience and knowledge. It posits that visual and conceptual manifestations of violence in Central American performance, conceptual art and installation extend beyond a critique of the state, and beyond the scope of political parties in perpetuating violent circumstances in these countries. It argues that instead artists use experimental practices in art to locate manifestations of racial violence in an historical system of domination and as a legacy of colonialism still witnessed, lived, and learned by multiple subjectivities in the region. In this postwar period artists move beyond the cold-war rhetoric of the previous decades and instead root the current social and political injustices in what Aníbal Quijano calls the `coloniality of power.' Through an engagement of decolonial methodologies, this dissertation challenges the label "political art" in Central America and offers what I call "visual disobedience" as a response to the coloniality of seeing. I posit that visual colonization is yet another aspect of the coloniality of power and indispensable to projects of decolonization. It offers an analysis of various works to show how visual disobedience responds specifically to racial and gender violence and the equally violent colonization of visuality in Mesoamerica. Such geopolitical critiques through art unmask themes specific to life and identity in contemporary Central America, from indigenous genocide, femicide, transnational gangs, to mass imprisonments and a new wave of social cleansing. I propose that Central American artists--beyond an anti-colonial stance--are engaging in visual disobedience so as to construct decolonial epistemologies in art, through art, and as art as decolonial gestures for healing.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Representations of Whiteness in the Black Imagination - hooks, bell (Belonging: A Culture of Place, 2019)
Searching the critical work of post-colonial critics, the author found much writing that bespeaks the continued fascination with the way white minds, particularly the colonial imperialist traveler, perceive blackness, and very little expressed interest in representations of whiteness in the black imagination. Some white people may even imagine there is no representation of whiteness in the black imagination, especially one that is based on concrete observation or mythic conjecture. Stereotypes black folks maintain about white folks are not the only representations of whiteness in the black imagination. Yet it is this representation of whiteness in the black imagination, first learned in the narrow confines of poor black rural community, that is sustained by the author travels to many different locations. Theorizing diverse journeying is crucial to the people understanding of any politics of location.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé

Imágenes de lo extraordinario. Memorias de un continente poblado por monstruos. - Gil, Slenka Leandra Botello; Camacho, Daianna Sierra (Cuadernos de Música, Artes Visuales y Artes Escénicas, 2021)
Este trabajo presenta los resultados de la investigación Imágenes de lo extraordinario: monstruos americanos del siglo XVI, proceso de creación artística desarrollado por los estudiantes del Semillero de Investigación en Artes Visuales (SINAV) del programa de Artes Visuales de la Universidad Nacional Abierta y a Distancia (UNAD) entre 2018 y 2019. Para analizar de manera crítica e histórica la construcción de identidades sobre lo latinoamericano, se tomó como marco de análisis la representación de lo monstruoso en los relatos y las imágenes construidas por los cronistas de Indias en el siglo XVI, los cuales marcaron procesos de marginalización cultural, construcción de subjetividades y dinámicas de poder, y presentaron al habitante americano como una otredad que estaba fuera de los límites de la cultura dominante occidental. Se presentan los postulados teóricos sobre lo monstruoso como marco para el análisis histórico y la creación de obra, con una metodología de trabajo colaborativo y en gran parte virtual. Posteriormente, se exponen algunos resultados de la investigación histórica que dan paso a detallar el proceso de creación de obra que culminó con la exposición de la instalación audiovisual Imágenes de lo extraordinario, así como con una amplia serie de ilustraciones contemporáneas sobre lo monstruoso y un producto digital en formato página web donde se presenta una cartografía de lo monstruoso en América Latina y se recogen las memorias de todo el proyecto. This work presents the results of the research Images of the Extraordinary: American Monsters of the 16th Century, artistic creation process developed by the students of the Research Seedbed in Visual Arts (SINAV, for its initials in Spanish) of the Visual Arts program of Universidad Nacional Abierta y a Distancia (UNAD) between 2018 and 2019. With the objective of analyzing, in a critical and historical way, the construction of identities on Latin American matters, the representation of the monstrous in the stories and images constructed by the chroniclers of the Indies in the 16th century was used as a framework of analysis. These chroniclers marked processes of cultural marginalization, construction of subjectivities and power dynamics, and presented the American inhabitant as an otherness that was outside the limits of the dominant Western culture. The theoretical postulates about the monstrous are presented as a framework for historical analysis and the creation of works, with a collaborative and largely virtual working methodology. Some results of the historical research are then presented, which gives way to detailing the process of creating work that culminated in the exhibition of the audiovisual installation Images of the Extraordinary, as well as a wide range of contemporary illustrations on the monstrous and a digital product in web page format where a cartography of the monstrous in Latin America is presented and the memories of the whole project are collected.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

Genealogías críticas de la colonialidad en América Latina, África, Oriente - Segato, Rita Laura, [et al.] (Universidad Nacional de San Martín, 2016)
El espesor de este libro es propio de este tiempo. Cuerpos que se desplazan en masivas inmigraciones huyendo de todo tipo de violencias alcanzan a más de sesenta millones de personas, la mayor cifra de refugiados desde la segunda guerra mundial. El mundo experimenta una crisis humanitaria sobrecogedora ante la cual las potencias apelan a los mismos discursos que ya Aimé Césaire o Fanon condenaran. Dramatismo del exilio de este nomadismo a escala planetaria, al cual Stuart Hall calificaría como “amensia imperial”. Genealogías críticas de la colonialidad en América Latina, África, Oriente es un libro que deja al descubierto la piel del mundo contemporáneo. Un hecho cultural disruptivo que, anudado a una genealogía latinoamericana abierta a sí misma y hacia Otros Sures se interroga sobre los intrincados modos de narrar y silenciar los pasados coloniales.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

Interview with author, Dr. Laura Pérez - Ramirez, Abraham
Interview with author, Dr. Laura Pérez, Professor of Ethnic Studies at UC Berkeley on her most recent book, Eros Ideologies: Writings on Art, Sprituality, & the Decolonial.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé

Eros ideologies. Writings on art, spirituality, and the decolonial. - Perez, Laura E (Duke University Press, 2019)
In 'Eros Ideologies' Laura E. Perez explores the decolonial through Western and non-Western thought concerning personal and social well-being. Drawing upon Jungian, people-of-color, and spiritual psychology alongside non-Western spiritual philosophies of the interdependence of all life-forms, she writes of the decolonial as an ongoing project rooted in love as an ideology to frame respectful coexistence of social and cultural diversity. In readings of art that includes self-portraits by Frida Kahlo, Ana Mendieta, and Yreina D. Cervantez, the drawings and paintings of Chilean American artist Liliana Wilson, and Favianna Rodriguez's screen-printed images, Perez identifies art as one of the most valuable laboratories for creating, imagining, and experiencing new forms of decolonial thought. Such art expresses what Perez calls eros ideologies: understandings of social and natural reality that foreground the centrality of respect and care of self and others as the basis for a more democratic and responsible present and future. Employing a range of writing styles and voices-from the poetic to the scholarly-Perez shows how art can point to more just and loving ways of being.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé

Revista N'oj Panel on Decolonizing Aesthetics - Latinx Research Center (2020)
The Latinx Research Center's Revista N'oj hosted a round table discussion on Decolonial Aesthetics titled, "Decolonizing Art & Praxis in the Time of Covid-19." The talk included Jesus Barraza, Dr. Guisela Latorre, Dr. Mauricio Barros de Castro, and Dr. Laura E. Pérez. The panel was moderated by Revista N'oj editor, Abraham Ramirez.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

La relación: pauta epistémica de la decolonialidad del saber desde el pensamiento afroantillano Los contornos del concepto en el Tratado del Todo-Mundo de Édouard Glissant (1928-2011) - Juncosa, José Enrique (Estudios Artísticos, 2016)
El presente artículo rastrea y explora el sentido poético y las posibilidades epistémicas del término relación a partir de la obra Tratado del todo-mundo, de Édouard Glissant, asumida como aporte del pensamiento afroantillano al proyecto del giro decolonial de los estudios interculturales latinoamericanos. En un primer momento, se identifican los rasgos y contornos operatorios de la identidad relación a partir de las siguientes claves de lectura: imaginería, poética y retórica, espiritualidad y ética, política y epistémica. En el segundo momento, se identifican las conexiones e implicaciones más relevantes para el contexto andino. De la exploración, se desprende que el pensamiento afrocaribeño de Glissant, contribuye a generar posibilidades discursivas potentes para enriquecer identidades abiertas en su diferencia y prácticas epistémicas sin amurallamientos identitarios o ilusiones uniformizantes. Finalmente, el aporte de Glissant, ofrece espacios de búsquedas a los movimientos sociales andinos para enriquecer sus prácticas de identidad en tanto relación, más allá de los esencialismos y la pretensión de raíz única. Cet article retrace et explore le sens poétique et les possibilités épistémiques du terme relation dans le traité d’Édouard Glissant, Traité du Tout-Monde, en tant que contribution afro-antillaise au projet du virage décolonial dans les études interculturelles latino-américains. Premièrement, nous identifions les traits et les contours opératoires de l›identité relationnelle à partir de clés suivantes : imagerie, poétique et rhétorique, spiritualité et éthique, politique et épistémique. Les liens les plus pertinents et les implications pour le contexte andin sont alors identifiés. De cette exploration, il est clair que la pensée afro-antillaise de Glissant contribue à générer de puissantes possibilités discursives pour enrichir des identités ouvertes dans leurs différences et leurs pratiques épistémiques, sans de murs identitaires ni d’illusions normalisatrices. Enfin, la contribution de Glissant ouvre des espaces de recherche pour les mouvements sociaux andins afin d’enrichir leurs pratiques d’identité en tant que relation, au-delà des essentialismes et de la prétention d’une seule origine.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Créateur.rice PANDC; _Nettoyé

Cultural code: video games and Latin America - Penix-Tadsen, Phillip (The MIT Press, 2016)
How culture uses games and how games use culture: an examination of Latin America's gaming practices and the representation of the region's cultures in games. Video games are becoming an ever more ubiquitous element of daily life, played by millions on devices that range from smart phones to desktop computers. An examination of this phenomenon reveals that video games are increasingly being converted into cultural currency. For video game designers, culture is a resource that can be incorporated into games; for players, local gaming practices and specific social contexts can affect their playing experiences. In Cultural Code, Phillip Penix-Tadsen shows how culture uses games and how games use culture, looking at examples related to Latin America. Both static code and subjective play have been shown to contribute to the meaning of games; Penix-Tadsen introduces culture as a third level of creating meaning. Penix-Tadsen focuses first on how culture uses games, looking at the diverse practices of play in Latin America, the ideological and intellectual uses of games, and the creative and economic possibilities opened up by video games in Latin America—the evolution of regional game design and development. Examining how games use culture, Penix-Tadsen discusses in-game cultural representations of Latin America in a range of popular titles (pointing out, for example, appearances of Rio de Janeiro's Christ the Redeemer statue in games from Call of Duty to the tourism-promoting Brasil Quest). He analyzes this through semiotics, the signifying systems of video games and the specific signifiers of Latin American culture; space, how culture is incorporated into different types of game environments; and simulation, the ways that cultural meaning is conveyed procedurally and algorithmically through gameplay mechanics. Source: Publisher
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Approches sociologiques; 2-Étude de la réception; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Race and Media: Critical Approaches - Lopez, Lori Kido (New York University Press, 2020)
1. Racism and Mainstream Media / Lori Kido Lopez -- 2. Image Analysis and Televisual Latinos / Mary Beltrán -- 3. Visualizing Mixed Race and Genetics / Meshell Sturgis and Ralina L. Joseph -- 4. Listening to Racial Injustice / Dolores Inés Casillas and Jennifer Lynn Stoever -- 5. Branding Athlete Activism / Jason Kido Lopez -- 6. The Burden of Representation in Asian American Television / Peter X. Feng -- 7. Indigenous Video Games / Jacqueline Land -- 8. Applying Latina/o Critical Communication Theory to Anti-Blackness / Mari Castañeda -- 9. Asian American Independent Media / Jun Okada -- 10. Remediating Trans Visuality / Amy Villarejo -- 11. Intersectional Distribution / Aymar Jean Christian -- 12. Podcasting Blackness / Sarah Florini -- 13. Black Twitter as Semi-Enclave / Raven Maragh-Lloyd -- 14. Arab Americans and Participatory Culture / Sulafa Zidani -- 15. Diaspora and Digital Media / Lia Wolock -- 16. Disrupting News Media / Meredith D. Clark -- 17. Latinx Audiences as Mosaic / Jillian M. Báez -- 18. Media Activism in the Red Power Movement / Miranda J. Brady -- 19. Black Gamers' Resistance / Kishonna L. Gray -- 20. Cosmopolitan Fan Activism / Susan Noh.
Keywords: 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Télé

Independent Videogames: Cultures, Networks, Techniques And Politics - Ruffino, Paolo (Routledge, 2021)
Independent Videogames investigates the social and cultural implications of contemporary forms of independent video game development. Through a series of case studies and theoretical investigations, it evaluates the significance of such a multi-faceted phenomenon within video game and digital cultures. A diverse team of scholars highlight the specificities of independence within the industry and the culture of digital gaming through case studies and theoretical questions. The chapters focus on labor, gender, distribution models and technologies of production to map the current state of research on independent game development. The authors also identify how the boundaries of independence are becoming opaque in the contemporary game industry – often at the cost of the claims of autonomy, freedom and emancipation that underlie the indie scene. The book ultimately imagines new and better narratives for a less exploitative and more inclusive videogame industry. Systematically mapping the current directions of a phenomenon that is becoming increasingly difficult to define and limit, this book will be a crucial resource for scholars and students of game studies, media history, media industries and independent gaming.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé

Video Games and the Global South - Penix-Tadsen, Phillip (ETC Press, 2019)
Redefines games and game culture from south to north, analyzing the social impact of video games, the growth of game development and the vitality of game cultures across Africa, the Middle East, Central and South America, the Indian subcontinent, Oceania and Asia.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Video Games Around the World - Wolf, Mark J. P. (MIT Press, 2015)
Video games have become a global industry, and their history spans dozens of national industries where foreign imports compete with domestic productions, legitimate industry contends with piracy, and national identity faces the global marketplace. This volume describes video game history and culture across every continent, with essays covering areas as disparate and far-flung as Argentina and Thailand, Hungary and Indonesia, Iran and Ireland.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

The Decolonial Turn in Media Studies in Africa and the Global South - Moyo, Last (Palgrave Macmillan, 2020)
This book develops a nuanced decolonial critique that calls for the decolonization of media and communication studies in Africa and the Global South. Last Moyo argues that the academic project in African Media Studies and other non-Western regions continues to be shaped by Western modernity’s histories of imperialism, colonialism, and the ideologies of Eurocentrism and neoliberalism. While Africa and the Global South dismantled the physical empire of colonialism after independence, the metaphysical empire of epistemic and academic colonialism is still intact and entrenched in the postcolonial university’s academic programmes like media and communication studies. To address these problems, Moyo argues for the development of a Southern theory that is not only premised on the decolonization imperative, but also informed by the cultures, geographies, and histories of the Global South. The author recasts media studies within a radical cultural and epistemic turn that locates future projects of theory building within a decolonial multiculturalism that is informed by trans-cultural and trans- epistemic dialogue between Southern and Northern epistemologies.
Keywords: 1-TV; 2-Approches sociologiques; 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Auteur.rice noir.e; _Nettoyé

Indigeneity and Decolonial Seeing in Contemporary Art of Guatemala. - Cornejo, Kency (FUSE Magazine, 2013)
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Coloniality at Large: Latin America and the Postcolonial Debate - Moraña, Mabel; Dussel, Enrique; Jáuregui, Carlos A. (Duke University Press, 2008)
Postcolonial theory has developed mainly in the U.S. academy, and it has focused chiefly on nineteenth-century and twentieth-century colonization and decolonization processes in Asia, Africa, the Middle East, and the Caribbean. Colonialism in Latin America originated centuries earlier, in the transoceanic adventures from which European modernity itself was born. Coloniality at Large brings together classic and new reflections on the theoretical implications of colonialism in Latin America. By pointing out its particular characteristics, the contributors highlight some of the philosophical and ideological blind spots of contemporary postcolonial theory as they offer a thorough analysis of that theory’s applicability to Latin America’s past and present. Written by internationally renowned scholars based in Latin America, the United States, and Europe, the essays reflect multiple disciplinary and ideological perspectives. Some are translated into English for the first time. The collection includes theoretical reflections, literary criticism, and historical and ethnographic case studies focused on Ecuador, Guatemala, Mexico, Brazil, the Andes, and the Caribbean. Contributors examine the relation of Marxist thought, dependency theory, and liberation theology to Latin Americans’ experience of and resistance to coloniality, and they emphasize the critique of Occidentalism and modernity as central to any understanding of the colonial project. Analyzing the many ways that Latin Americans have resisted imperialism and sought emancipation and sovereignty over several centuries, they delve into topics including violence, identity, otherness, memory, heterogeneity, and language. Contributors also explore Latin American intellectuals’ ambivalence about, or objections to, the “post” in postcolonial; to many, globalization and neoliberalism are the contemporary guises of colonialism in Latin America. Contributors : Arturo Arias, Gordon Brotherston, Santiago Castro-Gómez, Sara Castro-Klaren, Amaryll Chanady, Fernando Coronil, Román de la Campa, Enrique Dussel, Ramón Grosfoguel, Russell G. Hamilton, Peter Hulme, Carlos A. Jáuregui, Michael Löwy, Nelson Maldonado-Torres, José Antonio Mazzotti, Eduardo Mendieta, Walter D. Mignolo, Mario Roberto Morales, Mabel Moraña, Mary Louise Pratt, Aníbal Quijano, José Rabasa, Elzbieta Sklodowska, Catherine E. Walsh
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Europe (lieu de production du savoir); _Nettoyé

Writing Art Histories From Below: A Decolonial Guanaca-Hood Perspective - Cornejo, Kency (Latin American and Latinx Visual Culture, 2019)
As a teenager during my first internship at the Los Angeles County Museum of Art, a diversity initiative for inner-city youth, the education curator enthusiastically asked, “Who here would like to be an art historian!?” Like all the other Black and Brown inner-city kids, I laughed inside. My response was not due to a lack of art appreciation; I grew up in a family of refugees who were all self-taught artists back home in El Salvador, who taught me to draw before I learned to read. Nor was my response rooted in apathy for creative expression, for I was involved in art and theater from my elementary through my high school years. Art was such a natural part of my life that the idea of studying it seemed wasteful to me. The truth was, the internship was one of two jobs I was working to financially help my family and pay for my first year of community college. Hidden even deeper, though, I believed the museum world was not my world. I was a guanaca (the appellative given to people from El Salvador) whose family fled war and remained invisible in mainstream US Latinx history and culture. I was also from the hood—in my case Compton, California, a city made notorious by gangsta rap and police brutality. I believed that people like me guarded the art on the museum walls, cleaned the floors and bathrooms for visitors, and served the food at the high-priced café. People who looked like me, who came from where I did, did not determine what art could be, nor could we afford to buy it. We certainly did not write the history of art, for if we had, we would see ourselves represented on the walls.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; _Nettoyé

Sakahàn: art indigène international - Hill, Greg A.; Lalonde, Christine.; Hopkins, Candice (Musée des beaux-arts du Canada, 2013)
Sakahàn' celebrates a growing international commitment to the collection, study and exhibition of indigenous art. Featuring more than 75 artists from around the world, this remarkable project places indigenous art squarely at the centre of contemporary art produced today.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créateur.rice noir.e; 5-Créatrice; _Nettoyé

El lugar del arte en la opción por una desobediencia epistémica decolonial // The place of art in the option for decolonial epistemic disobedience - Bolaños, Martin (Hermeneutic : Revista Digital de Arte, Crítia y Filosofía, 2020)
The visualization of the ways of doing what is sensible in a globalized society is one more form of discipline of sensitivity and its poetics. The border between a colonized sensibility and an insurgent sensibility becomes blurred as the international distribution of the sensible assigns specific ways capable of domesticating the sensibilities that overwhelm it. Those sensitivities not that cannot be captured neither as merchandise, nor as an archive, nor as heritage. The overflow and excess of these sensitivities that have not been caught in the networks of an international art market jeopardize, by their very existence, the categories that aesthetics, as a modern-colonial discipline has produced to conceptualize and codify the sensitivities (isolationism) neutralized their capacities to witness historically subjugated life experiences. In this sense, decolonial stasis retrace the traced path, and one of the ways of retracing is to disarticulate or at least resignify words such as "art", "artist", "work", "production", "aesthetic", or "Poetic", among others.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

Close Encounters: The Next 500 Years - Farrell Racette, Sherry. (Plug In Editions., 2011)
Catalogue d'exposition publié à l'occasion de l'exposition tenue au Plug In Institute of Contemporary Art, Urban Shaman Contemporary Aboriginal Art, et Winnipeg Art Gallery, du 22 janvier au 8 mai 2011. Now is the moment to reconfigure our notions of time to reveal alternative ways of thinking and being for the future. In Close Encounters: The Next 500 Years Indigenous artists imagine the future within the context of present experiences and past histories. By radically reconsidering encounter narratives between native and non-native people, Indigenous prophecies, possible utopias and apocalypses, this exhibition proposes intriguing possibilities for the next 500 years. "We all in different measure have carved out the future," observes Hopi photographer and filmmaker, Victor Masayesva, in his book Husk of Time. "We are all clairvoyants, soothsayers, prophets, knowingly assuming our predictions. Close Encounters brings together over 30 Indigenous artists from across Canada, the United States, South America, Europe, Australia and New Zealand, including newly commissioned work from Rebecca Belmore, Faye HeavyShield, Kent Monkman, and Edward Poitras. Jimmie Durham's sculptural work A Pole to Mark the Centre of the World (at Winnipeg) will be an ongoing critique of widely held ideas surrounding space and location, while James Luna's poignant installation The Spirits of Virtue and Evil Await my Ascension, addresses issues of ritual and the passing of time. Close Encounters showcases artists and artworks that collectively invent provocative futures from a diversity of perspectives and practices. With its myriad histories, trajectories, tensions, collisions, and self-image(s), the city of Winnipeg offers an intriguing juxtaposition for these artistic mediations. Close Encounters: The Next 500 Years presents international Indigenous perspectives in a city that in many ways also epitomizes the future of Aboriginal people in Canada. Works in multiple venues throughout the city will serve as catalysts to invent different ways of thinking, acting, and being in the world of our shared future. At this pivotal moment in time, Close Encounters invites engagement with the speculative, the prophetic, and the unknown
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Épistémologies autochtones; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé